Pengukuran Kinerja Usaha Menggunakan Metode Balanced Scorecard : (Studi Kasus Pada CV XYZ) - Ridho Fadliansyah; Irawan Irawan; Dian Nirmala Dewi (FEB Universitas Maritim Semarang, 2025)
This study aims to measure the business performance of CV XYZ through the perspectives of finance, customers, internal business processes, growth and learning of the balanced scorecard method at CV XYZ in 2023. The data used is primary data, in the form of data from interviews with CV XYZ managers or those who have authority over CV XYZ business performance data. The results of the study can be concluded that based on research on the financial perspective, the results of the calculation of current ratio, revenue growth, debt to total assets, debt to equity, return on equity, return on assets and net profit margin get “good” criteria. In the customer perspective, the results of the calculation of customer retention get “sufficient” criteria, while the results of the calculation of customer acquisition and customer complaints get “good” criteria. In the internal business process perspective, the results of the calculation of minimize error rate and rework, and agreements with third parties get the “good” criteria. In the growth and learning perspective, the results of the calculation of employee retention get the criteria “sufficient”, employee training gets the criteria “good” and absenteeism gets the criteria “not good”.